Salvianolic Acid B Alleviates Limb Ischemia in Mice via Promoting SIRT1/PI3K/AKT Pathway-Mediated M2 Macrophage Polarization. (24th May 2022) - Niu, Wenhao; Wu, Feng; Cao, Wenyue; Chen, Yihong; Zhang, Yanda; Chen, Yasha; Ding, Ru; Liang, Chun
Abstract : Salvianolic acid B (Sal B) is an effective treatment agent for ischemic disease in China. However, Sal B's effects on peripheral arterial disease (PAD) and its mechanism remains poorly understood. Macrophage polarization plays a crucial role in PAD. Nevertheless, treatment modalities that increase the population of anti-inflammatory (M2) macrophages are limited. This study aimed to explore the protective effects of Sal B on limb perfusion and investigate the mechanism of Sal B-induced macrophage polarization. C57BL/6 male mice (6 weeks) were randomized into control, Model + NS, and Model + Sal B groups ( n  = 5). Then, we established a hind limb ischemia mouse model to assess the Sal B's role (15 mg/kg/d) in PAD. We quantified the blood perfusion via laser speckle contrast imaging (LSCI) and measured the capillary density and muscle edema with CD31 and H&E staining. The Sal B-induced macrophage polarization was confirmed by qPCR and ELISA. The results showed that the Sal B group exhibited a significant improvement in the blood perfusion, capillary density, muscle edema, and M2 markers gene expressions. Cell migration and tube formation were promoted in the endothelial cells stimulated with a culture supernatant from Sal B-treated macrophages. In contrast, endothelial functions improved by Sal B-treated macrophages were impaired in groups treated with SIRT1 and PI3K inhibitors. These findings provide evidence for Sal B's protective role in PAD and demonstrate the enhancement of macrophage polarization via the SIRT1/PI3K/AKT pathway.